EU11 Regular Economic Report, Issue #26, January 2013 - World Bank (Washington, DC, 2014)
The economic report comprises two parts: a macroeconomic report and a special topic on the issue of economic policy interest. According to the first part, in 2012 the EU11 economies have outperformed the rest of the European Union (EU). In the middle of a recession in the Euro area, the EU11 region is set to expand by about 1 percent in 2012. However, the recession in the Euro area continues to dampen the EU11 economic performance. With an uncertain economic outlook in the medium term, the EU11 need to pursue decisive economic policies on two fronts to safeguard and accelerate their growth momentum. First, a prudent macro-policy stance should continue to shore up the confidence of financial markets. Second, the medium-term economic growth potential of the EU11 can only be realized if structural barriers to economic activity are removed. Second, the current and projected low fertility levels for Europe imply that the region will go through an unprecedented process of population aging, causing dramatic changes in the age structure of European societies. These changes in the age structure can have significant effects on economic growth. This paper analyzes the quantitative impact of the projected demographic changes on economic growth through their effect on the factors of production, as well as the role that these will play in shaping income convergence in the region in the decades to come. The empirical results indicate that EU11 is likely to experience a sizable reduction in income per capita growth and thus in the speed of income convergence to the rest of the EU due to the expected demographic developments in the region. However, increasing labor force participation as well as improving the skill level of the labor force in the EU11 appears to be a powerful instrument for fostering economic growth and further convergence in the EU in the context of aging societies.